The process of decision-making of foreign direct investment in special economic areas - Vargas-Hernández, José G.; López-Mayorga, Vania Y. (DRd - Desenvolvimento Regional em debate, 2018)
The objective of this paper is to analyze the decision making process on foreign direct investment (FDI) as well as the location strategies used as the main objective which is the achievement of greater profits via cost reduction. Part of the assumption that the Special Economic Zones (ZEE) recently decreed (2016) offer tax incentives that allow them to reduce costs to foreign companies, encouraging them to establish them in these areas. A comparative analysis of the EEZs with the state of Jalisco as a reference, since this is characterized as an industrialized and attractive state for the arrival of FDI. The method used was a comparative analysis of the descriptive scope of variables such as population by age group, level of education and the Global Indicator of Economic Activity (IGAE), as well as the IED. Finally, the main conclusion is that the strength of these states under the EEZ regime is the Economically Active Population (EAP). However, the decree that establishes these special zones in Mexico must be accompanied by policies that strengthen the educational and social and security conditions in these States. Keywords: Special Economic Zones. Decision Making. Location Strategies.